2019
DOI: 10.1590/s0102-053620190115
|View full text |Cite
|
Sign up to set email alerts
|

Yield, frying quality, plant vigor, and maturity of potato clones

Abstract: The objective of this research was to evaluate advanced potato clones for tuber yield, frying quality, plant vigor, and maturity, grown from minituber seeds, and to assess correlations between these traits. Eight advanced potato clones of Embrapa Potato Breeding Program (F11-09-03, F05-11-03, F54-11-06, F141-11-01, C2718-12-09, C2718-24-09, C2743-09-09, and CL308) and three commercial cultivars (Agata, Asterix and BRSIPR Bel) were evaluated. Experiments were carried out in autumn 2017, in Canoinhas-SC and Pelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Higher dry matter provides advantages of higher processing yield, less fat absorption, better texture without affecting the taste. On the other hand, low sugar contents prevent the darkening of the processed potato products, which compromises the appearance and avor of the fried product (Silva et al 2019;Kammoun et al 2022). Tubers obtained in this study from BmI4-treated plants showed the lowest reducing sugars and higher dry matter (19.5%) compared to tubers of non-inoculated plants under salt stress conditions (12.59%).…”
Section: Discussionmentioning
confidence: 69%
“…Higher dry matter provides advantages of higher processing yield, less fat absorption, better texture without affecting the taste. On the other hand, low sugar contents prevent the darkening of the processed potato products, which compromises the appearance and avor of the fried product (Silva et al 2019;Kammoun et al 2022). Tubers obtained in this study from BmI4-treated plants showed the lowest reducing sugars and higher dry matter (19.5%) compared to tubers of non-inoculated plants under salt stress conditions (12.59%).…”
Section: Discussionmentioning
confidence: 69%
“…Plant vigor is influenced by nutrient uptake and utilization by the different genotypes. Numerous studies have reported correlations of medium magnitude between plant vigor and plant size, tuber number and tuber yield, indicating that the more vigorous plants produce larger, higher number and higher yield of tubers [20,21,22]. According to Salas, [14], genotypes with weak plant vigor have few leaves and thin stems.…”
Section: Discussionmentioning
confidence: 99%
“…The season had sufficient rainfall to support proper plant growth. Differences in tuber size influence growth and processing qualities [21]. According to Tessema et al, [27], large tubers have more sprouts and produce more stems per plant.…”
Section: Discussionmentioning
confidence: 99%
“…The plant vigor is an important trait for farmers’ selection process of a good potato variety. In the study to determine the correlations between plant vigor and plant size, tuber number, and tuber yield, it was found that the more vigorous plants produce larger number and high tuber yield (Silva et al., 2019). Bradshaw et al.…”
Section: Discussionmentioning
confidence: 99%